Analysis of heavy metal concentrations of ofia-imoka river inAwka town Southeast Nigeria for domestic purposes - Nwanna, Emmanuel Chukwudi; Maduegbuna, John Ikedinachukwu; Odeh, Calistus Princewill; Ekwueme, Godspower Onyekachukwu; Okadigwe, Emmanuel Igwebudu (Jurnal Pesona Indonesia, 2025)
Recognizing the heavy metal attributes of water is essential when handling resources, evaluating its purity, as well as tackling environmental issues. Water is an essential part of life and a vital resource for industrial, residential, and environmental uses. Because of the possible connections to cancer and other illnesses, the presence of heavy metal poisoning in rivers poses major health hazards through ingestion and skin exposure. The river's typical usage for drinking, cooking, and other domestic tasks are restricted since it flows via a channel that may have become polluted by manufacturing, agriculture, among other human activity. The sample was gathered, and its degree of contamination by heavy metals as well as appropriateness for household use were assessed. Lead (Pb), cadmium (Cd), mercury (Hg), chromium (Cr), iron (Fe), molybdenum (Mo), manganese (Mn), arsenic (As), cobalt (Co), nickel (Ni), silver (Ag), and calcium (Ca) are among the characteristics that were examined. Atomic Absorption Spectrometer (AAS) were used to analyze the metal content in water samples and contrasted with World Health Organization (WHO) permissible limits. All of the metrics, with the exception of nickel mg/l (0.011) and mercury mg/l (0.003), were found to be below WHO permissible levels. The administration of agricultural chemical products, growth in urbanization, industrialization, mining for minerals, and natural factors such as weathering of rocks are the main causes of this contamination. As a means to tackle pollution from heavy metals and safeguard human health, the study highlights the need for ongoing surveillance and focused mitigation techniques. Given the recommended values, the Ofia-Imoka river is unfit for human consumption since the levels of nickel, and mercury exceeded what the WHO considers safe.